2023
DOI: 10.1002/aenm.202203806
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of Ultrasmall Pt Clusters and Basic La2O2CO3 Supports Boosts the Reverse Water Gas Reaction Efficiency

Abstract: the most promising routes of the artificial carbon cycle, has aroused widespread concern and paves a new way to sustainably produce fuels and fine chemicals, but a validated process is still lacking both conceptually and practically. [1a] As the most fundamental route of CO 2 hydrogenation, the reverse-water gas shift (RWGS) reaction offers a chance to overcome the challenges. [2] Despite the catalytic process being no longer mysterious, the specific reaction rate achieved currently is still far from the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The nanotube with confinement effect could stabilize the Zn δ + sites, and CeO 2 with the Ce 3 + /Ce 4 + redox could inhibit the electron accumulation around the unsaturated site and thus prevent the reduction degradation of active Zn δ + sites during CO 2 electrolysis. [25][26][27][28] The hollow core-shell structure Zn δ + /ZnO/CeO 2 with a high selectivity of 76.9 % at À 1.08 V vs. RHE toward CO product and the CO selectivity in a long-term stability test over 18 h. In situ characterization and theoretical studies demonstrate that the energy barrier for the formation of *COOH is thermodynamically reduced by Zn δ + sites. And the confinement strategy ensures the stability of Zn δ + species, which contributes to maintaining the CO selectivity in a long-term stability.…”
Section: Introductionmentioning
confidence: 99%
“…The nanotube with confinement effect could stabilize the Zn δ + sites, and CeO 2 with the Ce 3 + /Ce 4 + redox could inhibit the electron accumulation around the unsaturated site and thus prevent the reduction degradation of active Zn δ + sites during CO 2 electrolysis. [25][26][27][28] The hollow core-shell structure Zn δ + /ZnO/CeO 2 with a high selectivity of 76.9 % at À 1.08 V vs. RHE toward CO product and the CO selectivity in a long-term stability test over 18 h. In situ characterization and theoretical studies demonstrate that the energy barrier for the formation of *COOH is thermodynamically reduced by Zn δ + sites. And the confinement strategy ensures the stability of Zn δ + species, which contributes to maintaining the CO selectivity in a long-term stability.…”
Section: Introductionmentioning
confidence: 99%
“…Pt-based catalysts are promising catalysts for the industrial RWGS process because of their excellent low-temperature activity (o270 1C), resistance to carbon deposition, and high CO selectivity at high temperatures. 71,72 However, limited by the high price and low natural abundance, Pt-based catalysts have not been used in the RWGS process on a large scale. One of the ways to solve this problem is to reduce the active center to the nanoscale as much as possible and even keep it highly dispersed at the atomic level.…”
Section: Pt-based Catalystsmentioning
confidence: 99%
“…The ultrasmall Pt clusters successfully integrated the unique surface states of single atoms and nanoparticles, thus achieving excellent catalytic performance. 71 Xing et al selected perovskite-type oxide SrTiO 3 as the support for constructing catalysts for CO 2 hydrogenation, and they found that the catalysts with SA sites (Pt 1 /SrTiO 3 ) exhibited higher CO selectivity than the catalysts with 2.72 nm NPs (Pt 7 /SrTiO 3 ). 74 They calculated the process of CO hydrogenation to CHO, and the reaction barriers for CO hydrogenation were 1.88 and 1.07 eV on Pt 1 /SrTiO 3 and Pt 7 /SrTiO 3 , respectively.…”
Section: Pt-based Catalystsmentioning
confidence: 99%
“…CO is an important intermediate from CO 2 hydrogenation and can be used directly as fuel or as feedstock in tandem reactions for a diverse range of fuel products . A variety of noble metal-based catalysts have been developed for reverse water gas shift (RWGS) reactions in recent years, but their high cost poses insurmountable challenges for commercial implementation. Non-noble metals for the RWGS reaction normally have poor activity and selectivity, especially at low temperatures, but there are exceptions, being highly dependent on the fine regulation of the local electronic structures for the active sites. …”
Section: Introductionmentioning
confidence: 99%